The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4028/www.scientific.net/amr.940.465
|View full text |Cite
|
Sign up to set email alerts
|

Network Access Control Technology Based on Trusted Label

Abstract: This research proposes network access control model based on the trusted label. The model combines the admission access control of network device and the transmission access control of data flow effective, and uses the trusted computing technology to ensure the credibility of the generated label, and adopts the access control based on the security domain to locate the granularity of access control to every packets, reduces the probability of successful attack to the network based on the information flow, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of Japanese scholar's research showed that the chromatism of transparent coating film was larger than nontransparent film, and the film has a shorter service life. The reason of the discoloration of coated wood would be wood extract soluble in coating dissolvent accumulates in the coating film caused the light induced discoloration [6][7]. Chinese scholars used Korean pine woods as the based material, the result showed that different species after coating radiated by UV light, the value of chromatism, lightness and yellow index change with the increase of irradiation time, different species present differences [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Japanese scholar's research showed that the chromatism of transparent coating film was larger than nontransparent film, and the film has a shorter service life. The reason of the discoloration of coated wood would be wood extract soluble in coating dissolvent accumulates in the coating film caused the light induced discoloration [6][7]. Chinese scholars used Korean pine woods as the based material, the result showed that different species after coating radiated by UV light, the value of chromatism, lightness and yellow index change with the increase of irradiation time, different species present differences [7].…”
Section: Introductionmentioning
confidence: 99%